(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2020)
The globalizatoin plays important role in the grow and development of tourism on the world market. The process of globalization has contributed in a political, economic and cultural sense, has directly affected the intensive growth of tourist travel. Increased mobility of people, the development of communication technologies and the emergence of the Internet have contributed to the strengthening of international over domestic tourism. Also, global tourism trends indicate a dominant influence on the process of globalization and its reflection on the tourism business. All this clearly shows that tourism in the future will have to adapt to phenomena outside its borders and thus will undoubtedly be the most important and at the same time the most sensitive branch of current and future trends that affect the demand and supply of tourism products and services. The main goal of this paper is to examine the impact of specific global trends on structural market changes in the demand for tourism, which is a prerequisite for the development of new trends in tourism. This research addresses the global status and trends of tourism, the contribution of the tourism sector to employment, gross domestic product and overall economic progress globally. The effects on tourism as a result of the development of global trends are further covered. However, globalization is a kind of phenomenon that has contributed to the mutual connection between the countries of the world.